Unexpected Dimerizations of Arylfurfural Oximes in their Mass Spectra - Aslam, Samina; Fatima, Aroog; Mustafa, Sidra; Zafar, Ansa Madeeha; Aslam, Noreen; Jabeen, Mussarat; Munawar, Munawar Ali; Khan, Misbahul Ain (Orbital: The Electronic Journal of Chemistry, 2024)
Various oximes of arylfurfural were found to eliminate an OH radical and dimerize during their mass spectral fragmentaion. A tentative fragmentation pattern is presented.